Spectroscopic Investigation of the Remote C–H Allylation of Amides via Photoredox and Nickel Dual Catalysis - Bourgois, Céline; De Kreijger, Simon; Xu, Bin; Tambar, Uttam K.; Troian-Gautier, Ludovic (Synlett, 2024)
The mechanistic details of a reported allylation reaction are investigated by means of Stern–Volmer experiments and nanosecond transient absorption spectroscopy. Both reference substrates, i.e., an allylic chloride and a trifluoroacetamide, are inefficient quenchers but large quenching rate constants are observed upon the addition of Ni(COD)2 and a bisoxazoline ligand. The large quenching rate constants and absence of observable photoproducts are consistent with a mechanism that operates by energy transfer between the excited-state iridium photosensitizer and the nickel complex.
Keywords: photoredox; energy transfer; mechanism; iridium; transient absorption; quenching; Stern–Volmer